Meio ambiente e patrimônio cultural: indicações geográficas de produtos e serviços amazônicos como elementos de proteção jurídica - Carvalho, Moysés Alencar de (2011)
The Geographical Indication may be conceptualized as an economical-juridical tool, related to the rights of industrial property, through which the State recognizes that a certain product or service carries peculiarities related and originated from geographical factors (natural and human) of a region, and thereby, that recognition generates exclusive economical usage rights for those who produce or perform those services there. In comparison with patents, the Geographical Indications present themselves as an option to the protection of traditional knowledge, once that some of the main characteristics of those models of reality understanding, so distinct from the western model, are based specially on collective principles. The rights generated by the Geographical Indications gather elements that, a priori, answer in a satisfactory way the specific needs raised from the traditional knowledge. For example, the benefits coming from the Geographical Indication are guaranteed for all the producers established in the area and, as it has no expiration date, those benefits can be maintained through all generations to come. There are a countless number of traditional peoples in the Amazon region, most of which hold great knowledge about the region and unique ways of creating, making and living, and deal with the astonishing diversity of scenarios and the complexity of the plot formed among the rivers and the mega biodiversity daily. The Geographical Indications may be a tool, still little used, to let those peoples improve their life quality, with sustainable practices and protecting their cultural patrimony. Keywords: Geographical Indication. Cultural Patrimony. Amazon. Traditional Knowledge.